Efficacy of Glutamine in Treating Severe Acute Pancreatitis: A Systematic Review and Meta-Analysis - Dong, Shi; Zhao, Zhenjie; Li, Xin; Chen, Zhou; Jiang, Wenkai; Zhou, Wence (Frontiers in Nutrition, 2022)
Objectives: The prognosis of severe acute pancreatitis (SAP) patients is closely related to early nutritional support. As an important nutrient for nutritional supplementation, changes in glutamine (Gln) level in the body reflect the severity of the patient's disease. However, there are currently inconsistent opinions on Gln nutrition therapy for SAP patients. To summarize and evaluate the advantages of Gln-supplemented nutritional therapy in SAP, we conducted this systematic review and meta-analysis. Methods: PubMed, Web of Science, the Embase, Cochrane Library and Chinese databases (CNKI, SinoMed, Wanfang and VIP) were systematically searched from inception through 31 October 2021 for eligible studies. Meta-analysis was conducted using Review Manager and Stata. Results: This meta-analysis included 28 randomized controlled trials (RCTs) with a total of 1714 patients. 30 primary indicators and 16 secondary indicators were analyzed. Compared with the control group, the addition of Gln helped to restore the liver, kidney and immune function of the patients, and increased serum albumin (SMD = 1.03, 95% CI: 0.74 to 1.31, P < 0.00001) and IgG level (MD = 1.03). 1.24, 95% CI: 0.82 to 1.67, P < 0.00001), decreased serum creatinine (Scr) level (MD = -12.60, 95% CI: -21.97 to -3.24, P = 0.008). Inflammatory markers such as C-reaction protein (CRP) were also significantly reduced (SMD = -1.67, 95% CI: -2.43 to -0.90, P < 0.0001). In addition, Gln also reduced patients' complication rate (OR = 0.37, 95% CI: 0.24 to 0.57, P < 0.00001) and mortality (OR = 0.30, 95% CI: 0.15 to 0.60, P = 0.0007), and reduced Total length of hospital stay (MD = -3.49, 95% CI: -5.05 to -1.93, P < 0.0001). Subgroup analyses found that parenteral Gln appeared to be more effective in reducing mortality. Conclusion: Gln-containing nutritional therapy is not routinely recommended, but it is a good choice for SAP patients. Although it has little effect on some indicator outcomes, in general, adding glutamine to nutrition is helpful for better prognosis of SAP patients. Keywords: Glutamine; Severe acute pancreatitis; Treatment; Meta-analysis